Optimization of the power output of a bare wind turbine by the use of a plain conical diffuser - Masukume, Peace-maker; Makaka, Golden; Mukumba, Patrick (MDPI, 2021)
A plain conical diffuser is optimized to augment the wind speed at the throat of the diffuser. The diffuser is used in the construction of a diffuser augmented wind turbine (DAWT) to augment the power output of a bare wind turbine (BWT). Experiments with empty conical diffusers were done to determine optimum geometrical parameters for the diffuser to achieve maximum wind speed augmentation. Using the obtained optimum geometrical parameters, an optimized plain conical DAWT was designed, constructed, and field tested. A twin decentralized wind energy system which comprised a BWT and the optimized plain conical DAWT was erected. The electrical power output from these systems was measured and compared. The optimized plain conical DAWT reduced the cut-in wind speed of a BWT from 2.5 m/s to 1.6 m/s. The power output was increased by a factor of 2.5. This power output is comparable to that of flanged diffusers. However, flanged-DAWTs are more inert due to the addition of the flange. Its response to wind speed and direction is slow as compared to plain conical DAWT. Thus, it cannot fully exploit the potential of the wind. Also, the addition of the flange increases its production cost. Therefore, plain conical DAWT can replace flanged-DAWT in wind power augmentation.